A certain class of starlike log-harmonic mappings - Aydoğan, Melike; POLATOĞLU, YAŞAR (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2014)
In this paper we investigate some properties of log-harmonic starlike mappings. For this aim we use the subordination principle or Lindelof Principle (Lewandowski (1961) [71). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Starlike log-harmonic mappings; Distortion theorem; Subordination principle